2012
DOI: 10.3141/2320-08
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing Young Germans’ Altered Car Use Patterns

Abstract: Since the turn of the millennium, car ownership and car travel among young German adults have decreased noticeably. This paper analyzes these changes in young Germans’ mobility behavior on the basis of a mobility diary survey and an income and expenditure survey. The decrease in car travel by young adults is linked to lower car ownership in this group. However, behavioral changes among car owners are far more important with regard to their overall decrease in car travel. Logistic regression was applied to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…Multimodality, the use of more than one mode of transportation during a specified time period, is gaining recognition as an important mechanism for reducing automobile dependence and increasing the sustainability of transportation systems by shifting some trips from automobiles to other modes (Chlond 2012;Kuhnimhof et al 2012b;Nobis 2007). For example, stagnating overall travel demand in western European countries has been connected to young adults who are displaying increasingly multimodal travel behavior and more diverse use of modes of transportation including driving, walking, cycling, and public transportation (Kuhnimhof et al 2012a;Nobis 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Multimodality, the use of more than one mode of transportation during a specified time period, is gaining recognition as an important mechanism for reducing automobile dependence and increasing the sustainability of transportation systems by shifting some trips from automobiles to other modes (Chlond 2012;Kuhnimhof et al 2012b;Nobis 2007). For example, stagnating overall travel demand in western European countries has been connected to young adults who are displaying increasingly multimodal travel behavior and more diverse use of modes of transportation including driving, walking, cycling, and public transportation (Kuhnimhof et al 2012a;Nobis 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that they are more likely to walk, bike, and use transit [26,27,[47][48][49][50]. Also, millennials/young adults are more multimodal compared to other generations [18,19,48,49,[51][52][53][54], own multiple mobility tools , and are open to use any mode that is most suitable for their needs [18]. They also tend to make fewer trips [24], own or use a car less [2,23,26,48], and are less likely to hold a valid driver's license or are more likely to delay obtaining a driver's license [50,51,55,56].…”
Section: Travel Trends Among the Two Generationsmentioning
confidence: 99%
“…Young Adults/Millennials: In the case of millennials, the gender gap in travel behavior is disappearing, indicating that the extent of variation in different of aspects of travel behavior between males and females is low compared to the older generation [48,49,54]. Compared to males, young females delay obtaining a driver's license [29,53,70], own/use automobiles less [48,54,[70][71][72], are less multimodal [53,54], and are more likely to use transit [27,53]. Another study found that males are less likely to be drivers and more likely to use active modes and transit [30].…”
Section: Personal Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…In dieser insgesamt dualistisch anmutenden Diskussion gilt Multimodalität als "nachhaltig", weil das ökologisch problematisierte Automobil innerhalb von multimodalen Verhaltensweisen in der Regel seltener und für kürzere Distanzen genutzt wird als bei seiner exklusiven Nutzung für alle Wege (Nobis 2007: 42 f.). Trotz insgesamt steigender Motorisierung und weitgehend stagnierender Pkw-Verkehrsleistung werden mit den jungen Erwachsenen bereits Kronzeugen für den Übergang angeführt (Kuhnimhof/ Wirtz/Manz 2012). Sie gelten als "New Generation" (Kuhnimhof/Buehler/Dargay 2011), womit eine historisch einmalige Trendumkehr in dieser Alterskohorte weg von der exklusiven Nutzung des privaten Automobils zum Ausdruck gebracht werden soll.…”
Section: Introductionunclassified